Reformulating the Regulation of Traditional Food-Making as Traditional Knowledge under Indonesia’s Communal Intellectual Property Law - Ni Nyoman Devi Kartikasari; I Made Dedy Priyanto (IJBLE Scientific Publications Community Inc., 2026)
This article examines the normative ambiguity surrounding the legal status of traditional food-making within Indonesia’s communal intellectual property regime, particularly under Article 8(a) of Government Regulation No. 56 of 2022 concerning Communal Intellectual Property. The provision lists “traditional methods or processes” as one form of Traditional Knowledge, but it does not define the phrase or expressly include traditional food-making. This lack of definitional precision creates legal uncertainty for communities whose culinary techniques, ingredient-selection practices, processing sequences, utensils, presentation rituals, and cultural meanings have been transmitted across generations. Using normative legal research, this article applies statutory, conceptual, systematic, teleological, and reform-oriented approaches to primary legal materials and selected scholarly sources on Traditional Knowledge, communal intellectual property, legal certainty, and utilitarian jurisprudence. The analysis shows that traditional food-making substantively satisfies the elements of Traditional Knowledge because it embodies communally held know-how, skills, technical practices, cultural values, and intergenerational transmission. Nevertheless, the absence of explicit normative clarification may generate inconsistent interpretation, weak inventory practices, and limited protection against unilateral commercial appropriation. The article proposes a reformulation of Article 8(a) by defining “traditional methods or processes” as including the entire sequence of traditional food-making, from local ingredient selection and processing techniques to traditional equipment, serving practices, and embedded cultural meanings. The article further recommends technical guidelines, systematic documentation, regional government participation, community education, benefit-sharing mechanisms, and accessible dispute-resolution procedures. The proposed reformulation is expected to strengthen legal certainty, enhance substantive justice for custodian communities, and align Indonesia’s communal intellectual property framework with the broader international discourse on Traditional Knowledge protection.